Climate Smart Disaster Risk Reduction: Indigenous Knowledge Practiced for Housing Technology in Coastal Zone of Bangladesh - Faisal, Md.; Biswas, A. K. M Abdul Ahad; Saha, Milton Kumar (TDMRC, Universitas Syiah Kuala, 2024)
The coastal region of Bangladesh is highly vulnerable to climate-induced natural disasters, with the population frequently experiencing various calamities. Over generations, inhabitants have developed indigenous knowledge and techniques to mitigate these impacts. This study examines traditional practices for enhancing housing resilience in Dashmina Upazila, Patuakhali District, a region prone to such disasters. By employing a multi-method approach, the research began with Focus Group Discussions (FGDs) involving 14 groups of 6-10 participants to explore indigenous knowledge on housing adaptation. This was followed by Key Informant Interviews (KIIs) with 16 individuals, including social leaders and NGO workers, to validate and expand on FGDs findings. Direct Observations through transect walks, Case Studies for in-depth analyses, and a review of secondary data from reports and articles complemented the primary data. Data were analyzed using Microsoft Excel 2010 for both quantitative summaries and descriptive qualitative analysis, with a SWOT analysis employed to assess the strengths, weaknesses, opportunities, and threats of these practices. The study identified effective traditional practices such as Raised Homestead Platforms and Deep-Rooted Pillars, which improved resilience against cyclones and flooding, although challenges such as erosion and material durability were noted. Additionally, Securing Roofs with crossbeams, Heavy Weight Hanging at roof corners, and Planting Disaster-Resistant Trees provided additional protection. Practices like Tying Houses to Trees or Pillars and using Lightweight Materials for riverbank erosion were found to be practical but faced durability issues. Overall, these traditional practices significantly enhance housing resilience, offering cost-effective solutions with actionable improvements. Recommendations include employing more durable materials and enhancing community awareness, highlighting the importance of integrating traditional knowledge with modern strategies for effective disaster risk reduction and climate adaptation. The study suggests that these indigenous practices should be taken into account in decision-making processes for planning any development projects aimed at reducing the risk of disasters